Pengaruh Atribut Produk, Celebrity Endorser dan Word Of Mouth terhadap Keputusan Pembelian produk Kosmetik Wardah - Annisa Putriani (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to test the effect of product attributes, celebrity endorser and word of mouth of product purchase decisions wardah cosmetics. the population is students S1 faculty of Economics university sarjanawiyata tamansiswa Yogyakarta who bought wardah cosmetic products less than 3 months. the study sample used 100 students. technique analysis using multiple analysis techniques which is supported by the t test, F test and coefficient of determination test with the help of the SPSS for windows 18.0 program. Result of research indicate that product attribute have a positive and significant effect on purchasing decision. celebrity endorser have a positive and significant effect on purchasing decision. word of mouth positively and significantly affect the purchase decision. product attribute, celebrity endorser, and word of mouth together simultaneously have a positive effect and significant to the purchase decision. Keywords: Product attribute, Celebrity endorser, Word of mouth and purchasing decisions.